HISTORISITAS HADIS MASA NABI, SAHABAT, TABI’IN DAN ATBA’ AL-TABI’IN - Ali Abdur Rohman; Intan Wulansari (CV. Adiba Aisha Amira, 2023)
This article discusses the history of the development of hadith during the time of the Nabi, Sahabat, Ta'abi'in, and Atba'al-Ta'abi'in and . The purpose of writing this article is to find out the state of the hadith at that time and also the way of conveying and receiving the hadith at that time, in addition to several other things related to it. This article is written using library research methods and a historical approach to make it easier to identify the state of hadith during the time of the Nabi, Sahabat, Ta'abi'in, and Atba'al-Ta'abi'in. The Prophet's era was the time of al-wahy wa al-takwin (the descent of revelation to Allah's Messenger and direct recitation to the Saha'bat). Sahabat, era al-tasabbut, wa al-iqlal min al-riwayah (hadith passage restriction). Tabi'in, the era of